Efficiency Of Marble Filter System For Groundwater Treatment - Mohd Akhir, Muhammad Fitri (2019)
Recently, El Nino heatwave phenomena has attacked Malaysia and consequently, the water level of three dams in Malaysia have fallen below the critical level. In order to solve this water shortage crisis, groundwater is indeed the best source of water for human beings as its nature of being located deep down beneath the earth has protected it from the exposure to the heatwave, thus would not be dried up as fast as compared to the surface water. However, the contamination of groundwater is inevitable and uncontrollable, yet it can still be treated economically. In this case, a 55.6m tube well located inside the Engineering Campus of Universiti Sains Malaysia was used as a groundwater sample in this research. It is found that the groundwater is highly contaminated by natural sources and human activities. Originally, the colour of the groundwater is yellowish green and emits H2S gas, but due to the oxidation reaction, it immediately changes its colour to black which is FeS precipitate in 40 seconds after being exposed to the air. A high concentration of salinity (5.1 ± 0.1 ppt), high concentration of NH3N, and various elements have also been detected in the groundwater sample. Due to this condition, groundwater is classified as class IV based on the water quality index Malaysia standards and considered to be harmful to human. To overcome this issue, a research has been carried out to find a way to make the groundwater to become a safe water resource to human beings and it has been proven that marble is one of the best filter media for groundwater resources. The properties of marbles which consist of 97% of CaCO3 have successfully enhanced the redox reaction of the contaminants, subsequently increase its precipitation rate and ease the filtration process. In term of the filter media size, it has found that the sand size is much better than the pebble size in removing the groundwater contaminants. The sand size of marble able to remove most of the groundwater contaminants with a percentage of above 90% and whereas some other elements such as Al, Ba, and Ca could be removed only above 70%. Nonetheless, the concentration of these elements after filtration are still below the threshold limit of the drinking water standard based on NWQS Malaysia, EPA, and WHO. As a result of the high removal efficiency of groundwaters' contaminants, it has achieved a water quality result of class I and class II. On the other hand, marble in pebble size produce a water quality in class III.